Vertical product differentiation, prominence, and costly search - Roberto Rozzi; Stefanie Y. Schmitt (Bamberg University, Bamberg Economic Research Group (BERG), 2024)
In many markets, firms offering low-quality goods are more prominent than firms offering high-quality goods. Then, consumers are perfectly informed about the good of the prominent low-quality firm but incur search costs to bring the high-quality good of a competitor to mind. We analyze under which circumstances the less-prominent firm has an incentive to invest in high quality. We investigate two scenarios: (i) homogeneous and (ii) heterogeneous search costs. If search costs are homogeneous, the less-prominent firm produces highquality goods for sufficiently low search costs, and an increase in search costs reduces the range of values for which the less-prominent firm invests in high quality. In contrast, if search costs are heterogeneous, the less-prominent firm produces high-quality goods for sufficiently high search cost heterogeneity, and an increase in average search costs expands the range of values for which the less-prominent firm invests in high quality.
Keywords: D43; D83; L13; 330; consideration sets; duopoly; prominence; search costs; vertical product differentiation